MINAT MAHASISWA MENGGUNAKAN FINTECH DI ERA INKLUSI KEUANGAN - Aurellia, Icha; Ahda Aura Azani; Dwi Natasyah Putri; Fitra Sonia; Muhammad Ilmi Kautsar; Wanda Pratiwi; Bahrudi Efendi Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the level of student interest in using financial technology (fintech) services in the era of financial inclusion. Using a descriptive quantitative approach, data were collected through an online questionnaire from 100 university students in Pematangsiantar. The findings show that the majority of respondents perceive fintech applications as easy to use, offering fast and practical transactions with user-friendly interfaces. Security is considered relatively good, although concerns about potential fraud still exist. In addition, peer influence and social media play a significant role in encouraging students' interest in using fintech services. The three dominant factors influencing interest are ease of use, perceived security, and social influence. These findings indicate that fintech has become a preferred financial solution among the younger generation, in line with the growing trend of financial inclusion in Indonesia. This study recommends enhancing digital financial literacy to help students better understand both the benefits and risks of fintech, thereby supporting more inclusive and sustainable financial development.